2017
DOI: 10.1007/s00296-017-3674-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-citrullinated protein antibodies are associated with decreased bone mineral density: baseline data from a register of early arthritis patients

Abstract: Since the previous studies showed that anti-citrullinated protein antibodies (ACPA) can induce osteoclasts differentiation and activation, even before arthritis onset, the aim of our study was to determine whether ACPA-positivity is associated with lower bone mineral density (BMD) at baseline visit of a register of early arthritis (EA) patients. The study population comprised 578 patients (80% females) from our EA clinic with a median disease duration, 5.1 months (p25–p75: 6–8); median age, 53.6 years (41.9–66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
35
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 22 publications
(45 reference statements)
6
35
3
Order By: Relevance
“…Both previous studies [ 17 , 18 ] pertaining to the association of anti-CCP and BMD in patients with early RA revealed a negative effect of anti-CCP+ on BMD at all measured sites, a finding that is inconsistent with those of the present study and other series on established RA [ 13 , 15 ]. There are several possible explanations for the different observations between the studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Both previous studies [ 17 , 18 ] pertaining to the association of anti-CCP and BMD in patients with early RA revealed a negative effect of anti-CCP+ on BMD at all measured sites, a finding that is inconsistent with those of the present study and other series on established RA [ 13 , 15 ]. There are several possible explanations for the different observations between the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent publication by Wysham et al also demonstrated that a high positive anti-CCP level and appendicular lean muscle mass were associated with FN BMD in established RA [ 16 ]. Llorente et al reported that patients with early RA with anti-CCP+ had lower BMD than the anti-CCP− control subjects at the lumbar spine, FN, and hip [ 17 ]. Bugatti et al also demonstrated that anti-CCP+ patients with early untreated RA had lower BMD than their anti-CCP− counterparts at the lumbar spine and hip [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of reduced systemic BMD in early stages of the RA indicated that while synovial inflammation may take a long time to produce systemic effects such as significant generalized BMD changes [25], reduced BMD in early stages of RA appears to be coupled with autoimmunity. Relevant to this concept, our results had confirmed the recent evidence that link the ACPA and RF to reduced BMD in patients with early RA [21,24].…”
Section: Discussionsupporting
confidence: 89%
“…The age of the women in the study of Forslind et al ranged from 55 to 61 years which may explain for the higher proportion of the reduced bone mass than in our study. The inclusion of premenopausal females, the short duration of RA symptoms, all patients had an active disease and lack of treatment could exclude the association of traditional osteoporosis risk factors or the disease related factors to the reduced BMD in our patients with early RA in agreement with earlier studies [21] and in contrast to findings of other studies that enrolled patients with early RA but with longer disease duration or variable treatment [22][23][24].…”
Section: Discussionsupporting
confidence: 86%
“…It is known that low BMD, measured with digital X ray techniques or dual‐energy X‐ray absorptiometry (DXA), is significantly associated with bone erosions in RA patients . Recently, cortical thinning and fenestration have been observed before the clinical onset of arthritis in subjects with anti‐citrullinated protein antibodies (ACPAs), and ACPAs have a negative titer‐dependent effect on BMD . ACPA titer is a well‐known risk factor for bone erosions in RA …”
mentioning
confidence: 99%